Utilization of Domestic Sewon Bantul Sewage Sludge as Raw Material for Granular Organic Fertilizer (GOF) - Ryan Bazaliel Alexandro Timpua; Warsiyah Warsiyah; Endah Ayuningtyas; Rita Dewi Triastianti (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Domestic wastewater treatment plant (WWTP) sludge still contains organic matter and nutrients, indicating its potential for beneficial reuse. This study aimed to analyse the physicochemical characteristics of dried sludge from Sewon WWTP, Bantul Regency, and to evaluate its potential as a raw material for granular organic fertilizer through physical stabilisation without active composting. Dried sludge obtained from the sludge drying bed was formulated into four treatments: 100% sludge (F1), sludge combined with cattle manure (F2), sludge combined with fermented organic fertilizer mijongan (F3), and sludge combined with rice husk (F4), each at a 1:1 ratio. The processing stages included crushing, mixing, manual granulation using starch as a binder, and laboratory analysis of pH, moisture content, organic carbon, total nitrogen, total phosphorus, total potassium, and C/N ratio, with results compared against national solid organic fertilizer standards. The results showed that all formulations met the requirements for pH and organic carbon content. Variations were observed in moisture content, total nitrogen, and C/N ratio. Total phosphorus and potassium did not meet the minimum standard of ?2% across any of the formulations. The F4 formulation (sludge combined with rice husk) demonstrated the most balanced physicochemical quality, with a moisture content of 7.77%, total nitrogen of 2.15%, and a C/N ratio of 16.96. Overall, Sewon WWTP sludge shows potential as a raw material for granular organic fertilizer; however, further formulation optimisation is required to meet the minimum standards for phosphorus and potassium content.